JAJAK PENDAPAT MASYARAKAT TENTANG LAYANAN SMART CITY DI KOTA MAGELANG - Arif Barata Sakti; Eny Sulistyowati; Yun Arifatul Fatimah; Emilya Ully Artha (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
Community Polling Activities in 2019 focus on the theme of smart city. The purpose of this activity is to obtain studies and recommendations on the results of research and studies as material for policy making. The purpose of this activity is to find out people's perceptions about the application of smart city in Magelang Municipality. The method used in this activity is direct observation to the people of Magelang Municipality, namely through interviews and semi-open questionnaires, using google form as a means of collecting respondent data. The results of the poll showed that the majority of respondents thought that the problems in the Magelang Muncipality could be overcome by utilizing information technology applications. This shows that the use of the Internet of Things (IoT) is a must to help the application of smart city. There are several problems identified in Magelang Municipality, namely: Public Transportation; Parking; Information on City Government Events/Activities; Licensin/Legality; Urban planning; University Information; Cleanliness of Public Facilities; Tourism spot; Hotel/Lodging; City/Disaster Security; Health, Environmental Sanitation; and Human Resources (HR)/Job Vacancy Information. The main problem that is desired to be overcome is public transportation (99.78%). The conclusion from the implementation of this activity is that public services in the Magelang Municipality are complete and numerous, but they have not been able to provide maximum services because they have not been integrated between the Regional Device Organization, making coordination difficult, almost all problems in the Magelang Municipality are considered to be resolved with the help of IT. Recommendations that can be followed up by the Magelang Municipality Government are the socialization to the people of Magelang Municipality for the introduction and development of smart cities, making a big data development scheme, and the introduction of the